Analisis Integrasi Teknologi Digital pada Buku Kemendikbud untuk Meningkatkan Kompetensi Berbahasa Indonesia pada Pemelajar BIPA - Dzakiroh, Azmilatudz; Asteria, Prima Vidya; Savitri, Agusniar Dian; Ahmadi, Anas (Paedagogie, 2026)
This study aims to analyze the level of digital technology integration in Indonesian for Foreign Speakers (BIPA) textbooks published by the Ministry of Education and Culture (Kemendikbud) using the SAMR (Substitution, Augmentation, Modification, Redefinition) framework. A qualitative descriptive method was applied to seven levels of BIPA textbooks (Teaching materials 1 to teaching materials 7). Data were collected through document analysis of all units in each textbook, and analyzed by identifying and classifying technology-related activities into the four SAMR levels. Results indicate that the majority of BIPA textbooks remain at the Substitution level, with audio replacing conventional dialogue texts as the dominant pattern. Some books reach the Augmentation level through internet-based supplementary references, and the Modification level through access to electronic media and online applications. Only teaching materials 6 and teaching materials 7 achieved the Redefinition level, through the use of the MYOB accounting application and video recording tasks for digital platforms. This study concludes that technology integration in Kemendikbud's BIPA textbooks remains predominantly substitutive and needs to be elevated to a transformative level to support more authentic language competencies relevant to the digital era.